Novel Thermo-Halotolerant Bacteria Bacillus cabrialesii Native to Qatar Desert: Enhancing Seedlings’ Growth, Halotolerance, and Antifungal Defense in Tomato - Fatma Masmoudi (16819554) (2024)
Soil salinization and freshwater scarcity are the major challenges threatening conventional agriculture development due to their negative impacts on plant growth and productivity. Fungal infections accentuate these challenges and pose a threat to global food security. Thermo-halotolerant bacteria exhibit a great ability to eradicate phytopathogen proliferation, enhance agricultural yields, and enable the use of saline water for irrigation in arid and semi-arid regions characterized by increasing temperatures and harsh climates. Ten novel halotolerant bacteria isolated from Qatar desert environment and coastline were screened in vitro for their halotolerance, thermotolerance, and plant-growth-promoting potential. Among these, five strains showed significant ability to produce cell-wall degrading enzymes, ACC-deaminase, siderophores, solubilize phosphorous, fix nitrogen, inhibit fungal proliferation, and form biofilms. Particularly, Bacillus cabrialesii strain HB7 displayed interesting potential to eradicate gray mold disease on post-harvested tomato fruits Solanum lycopersicum var. cerasiforme and promote seeds germination and seedlings growth under saline conditions. Scanning electron microscopy evidenced that HB7 is an endophytic strain, capable of forming protective biofilm around tomato seedling roots. This biofilm may play an important role in protecting internal plant tissues and preventing salt infiltration. These findings support the use of Bacillus cabrialesii strain HB7 as an efficient biofertilizer, offering a pathway to sustainable agricultural practices that leverage saline water resources for irrigation. Other Information Published in: Journal of Plant Growth Regulation License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00344-024-11460-2